Novel “Nonkinase” Phorbol Ester Receptors: The C1 Domain Connection - Kazanietz, Marcelo G. (Molecular pharmacology, 2002)
In recent years, there have been great advances in our understanding of the pharmacology and biology of the receptors for the phorbol ester tumor promoters and the second messenger diacylglycerol (DAG). The traditional view of protein kinase C (PKC) as the sole receptor for the phorbol esters has been challenged with the discovery of proteins unrelated to PKC that bind phorbol esters with high affinity, suggesting a high degree of complexity in the signaling pathways activated by DAG. These novel “nonkinase” phorbol ester receptors include chimaerins (a family of Rac GTPase activating proteins), RasGRPs (exchange factors for Ras/Rap1), and Munc13 isoforms (scaffolding proteins involved in exocytosis). In all cases, phorbol ester binding occurs at the single C1 domain present in these proteins and, as in PKC isozymes, ligand binding is a phospholipid-dependent event. Moreover, the novel phorbol ester receptors are also subject to subcellular redistribution or “translocation” by phorbol esters, leading to their association to different effector and/or regulatory molecules. Clearly, the use of phorbol esters as specific activators of PKC in cellular models is questionable. Alternative pharmacological and molecular approaches are therefore needed to dissect the involvement of each receptor class as a mediator of phorbol ester/DAG responses.